Exploring the Paradox of Natural Beauty and Management Neglect of Fodo Beach - Harefa, Afore Tahir; Gea, Juardiman Putra; Gea, Danieli; Gea, Irawan Jeprianus (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Coastal tourism remains a primary driver of regional development, yet its sustainability is frequently compromised by the quality of local governance. Fodo Beach in Gunungsitoli presents a unique paradox where significant natural aesthetic capital is currently overshadowed by operational decline and infrastructure decay. This study aims to explore the disconnect between the destination’s natural potential and its management reality while identifying the specific factors contributing to its stagnation. Using a qualitative case study approach, data were gathered through in-depth interviews with family owners, visitors, and tourism officials, supplemented by field observations and thematic analysis. The findings reveal a "Strategic Gap" where high-value natural assets are neutralized by a lack of professional hospitality standards and deteriorating facilities. The informal, family-based management structure serves as the primary barrier to professionalization, characterized by a lack of standard operating procedures and "resource poverty" in human capital. Consequently, Fodo Beach has transitioned into a decline stage within its lifecycle, where enduring natural beauty can no longer compensate for systemic management neglect. This study implies that reversing the decline requires a fundamental shift from informal family-centric ownership toward professionalized governance or public-private partnerships to restore the destination's competitiveness.